PRC overseas political activities risk, reaction and the case of Australia - Chubb, Andrew (Whitehall papers, 2021)
Political elites in liberal democracies are showing heightened concern about threats to national security from the overseas political activities of the People's Republic of China (PRC) and its supporters. This Whitehall Paper argues that an effective liberal democratic policy response requires careful disaggregation of distinct sets of risks: to national security; civil liberties; and academic freedom. Although widely cited as a model to follow, Australia's response to these issues illustrates how aggregation of these diverse risks into a singular national security threat - commonly labelled 'Chinese influence' - can produce alarmist public policy discourse, legislative overreach and mismatched institutional responsibilities. The Paper suggests a set of measures for liberal democracies to manage their engagement with China's powerful and increasingly authoritarian party-state.